PENGARUH PEMBERIAN MOBILISASI DINI TERHADAP PENURUNAN TINGKAT NYERI PADA PASIEN POST LAPARATOMI - Milta Milta; Matius Paundanan; Djuwartini Djuwartini (KEWINUS: Jurnal Keperawatan dan Kesehatan, 2024)
Laparatomy is an invasive technique performed to open and expose the treated body part. Post laparatomy patients will experience pain, early mobilization is one of the non-pharmacological techniques to reduce pain. The purpose of the study was to analyze the effect of early mobilization on reducing pain levels in post laparatomy patients in the inpatient room of RSUD Undata , Central Sulawesi Province. This study used a quantitative method with a Quaisy Experiment Design approach, which is a one-group strategy consisting of pretest and posttest. The sampling technique used purposive sampling as many as 18 respondents. The research instrument used Comparative Pain Scale and observation sheet. Data analysis using paired t-test. The results showed that the average pain level experienced by respondents before early mobilization was on a severe scale (Value 7) and the average pain level after early mobilization was on a moderate scale (Value 6). The paired t-test test results obtained a p-value of 0.000 (<0.05), so it was concluded that there was a significant difference in the pain scale in the pre-test and post-test. The results of this study indicate that early mobilization has a significant effect on reducing the pain level of postoperative laparatomy patients.